PENGEMBANGAN MODUL MELAKUKAN KOMUNIKASI MELALUI TELEPON PADA STANDAR KOMPETENSI MENGAPLIKASIKAN KETERAMPILAN DASAR KOMUNIKASI DI KELAS X ADMINISTRASI PERKANTORAN SMK NEGERI 10 SURABAYA - AYU KUSUMANINGRUM, DINDA (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
ABSTRACT   Module is a learning material instrument presented in systematic manner hence it can be learned independently or without teacher assigned for learning process by communicating via telephone. In the development process it used 4D development in Trianto as foundation. Trial subject in this module development is material expert and 15 students of SMKN 10 Surabaya. Instrument used was suitability assessment by material expert and student opinion. Overall result of validation from experts and limited trial had percentage means of 91.93%. Hence it can be concluded that module performing communication via telephone develop by researcher. Keywords: Module, Performing communication via telephone, applying communication basic skill, 4D Development.